Entre cortiços e sobrados: representações, discursos e imaginários sobre a população do Brasil em O Cortiço de Aluísio Azevedo - SILVA, Francinaldo Pereira da (2021)
This work aims to analyze the naturalistic work of Aluísio Azevedo – the novel O Cortiço (1890), from a perspective of sociological bias, addressing the aspects of representations, discourses and imaginaries constructed in the link of the narrative about the Brazilian population in the nineteenth century. , investigate the function that justifies the (dis)social qualification of these representatives of Brazilian society, through the discourses and imaginaries ingrained in the work. To this do so, at first we discuss a central discussion of theoretical basis about the relationship between literature and society, and discourse and narrative, which from Aristotle's Poetic Art is expensive to literary studies. Thus, we brought to this discussion the theoretical postulates of Antonio Candido (2006, 2007), Mikhail Bakhtin (2002, 2003), Gérard Genette (2015, 2017), among others. Our second moment deals with a discussion about the naturalistic aesthetics and the critical fortune of The Tenement, revisiting Werneck Sodré (1965), Émile Zola (1982, 1995), Alfredo Bosi (2015), Antonio Candido (1974, 1991), Haroldo Sereza (2012), among others. Finally, we analyze the development of the characters in the face of the discourses that appear in the novel, from the urban development to the issue of animality. Thus, we divided our analysis into three parts, in which we punctuated questions about race, moment and a half, reflected in the differentiation and overcoming of the tenement dichotomy x leftover.